2012
DOI: 10.1097/spv.0b013e31826fb8d3
|View full text |Cite
|
Sign up to set email alerts
|

Health Literacy and Disease Understanding Among Aging Women With Pelvic Floor Disorders

Abstract: OBJECTIVES Few studies on health literacy and disease understanding among women with pelvic floor disorders have been published. We conducted a pilot study to explore the relationship between disease understanding and health literacy, age, and diagnosis type among women with urinary incontinence and pelvic organ prolapse. METHODS Study subjects were recruited from urology and urogynecology specialty clinics based on a chief complaint suggestive of urinary incontinence or pelvic prolapse. Subjects completed q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 12 publications
0
47
0
Order By: Relevance
“…The articles that considered health literacy the response variable (n=11, 40.7%) (14,15,17,21,22,26,27,31,32,36,37) include the 5 instrument validation studies (18.5%) (22,26,31,32,37) , 4 population-based studies (14.8%) -2 in Taiwan (14,15) , 1 in Finland (27) and 1 intercontinental study (17) , -and 2 studies with diabetic patients (7.4%), carried out in Japan (21,36) . As for place of origin, studies carried out in North America predominated (n=13; 48.1%) (11,12,(18)(19)(20)23,24,(30)(31)(32)(33)(34)(35) , all of them in the United States. Six European studies were identified (22.2%): 2 from the Netherlands (7.4%) (13,29) , 1 from Ireland (3.7%) (25) , 1 from Finland (3.7%) (27) , 1 from Serbia (3.7%) (22) , and 1 jointly developed by 15 European countries (3.7%) (16) .…”
Section: Methodological and Contextual Characteristics Of The Selectementioning
confidence: 99%
See 4 more Smart Citations
“…The articles that considered health literacy the response variable (n=11, 40.7%) (14,15,17,21,22,26,27,31,32,36,37) include the 5 instrument validation studies (18.5%) (22,26,31,32,37) , 4 population-based studies (14.8%) -2 in Taiwan (14,15) , 1 in Finland (27) and 1 intercontinental study (17) , -and 2 studies with diabetic patients (7.4%), carried out in Japan (21,36) . As for place of origin, studies carried out in North America predominated (n=13; 48.1%) (11,12,(18)(19)(20)23,24,(30)(31)(32)(33)(34)(35) , all of them in the United States. Six European studies were identified (22.2%): 2 from the Netherlands (7.4%) (13,29) , 1 from Ireland (3.7%) (25) , 1 from Finland (3.7%) (27) , 1 from Serbia (3.7%) (22) , and 1 jointly developed by 15 European countries (3.7%) (16) .…”
Section: Methodological and Contextual Characteristics Of The Selectementioning
confidence: 99%
“…Concerning design, the majority of the studies was observational and cross-sectional (n= 22; 81.5%) (11,12,(14)(15)(16)(17)(18)(20)(21)(22)(24)(25)(26)(27)(28)(29)(30)(31)(32)(35)(36)(37) , and some received additional specifications: 3 were pilot studies (11.1%) (20,24,25) , 4 were multi-center studies (14.8%) (11,16,17,30) , and 5 focused on validation of assessment instruments (18.5%) (22,26,31,32,37) . Randomized clinical trials -studies that present higher levels of scientific evidence -totaled only 4 occurrences (14.8%) (19,23,33,34) , and 2 of them were multi-center studies (7.4%) (33,34) .…”
Section: Methodological and Contextual Characteristics Of The Selectementioning
confidence: 99%
See 3 more Smart Citations